Open Strategy: Dimensions, Dilemmas, Dynamics - Hautz, Julia; Seidl, David; Whittington, Richard (Long range planning, 2017)
Responding to increasing practitioner and academic interest in Open Strategy, this article builds on recent theoretical and empirical studies in order to advance research in the following ways. We begin by developing a definition of Open Strategy that emphasizes variation along the two dimensions of transparency and inclusion, as well as the dilemmas and dynamics inherent in its practices. We identify five dilemmas in particular: those of process, commitment, disclosure, empowerment and escalation. We continue by exploring key dynamics in Open Strategy, including both movements along the dimensions of transparency and inclusion, and movements between the two dimensions. Respecting the acute dilemmas of Open Strategy, we allow in each case for movement away from greater openness. The article concludes by proposing an agenda for future research on Open Strategy.